A plating aid liquid for hot galvanizing process, a preparation method thereof and a hot galvanizing process
By using a fluxing solution composed of zinc chloride, ammonium chloride, potassium fluoride, and a composite surfactant, the problem of incomplete coating in the hot-dip galvanizing process is solved, and the uniformity and corrosion resistance of the coating are improved, making it suitable for hot-dip galvanizing processes.
Patent Information
- Application Number
- CN202310718700.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2043-06-16
AI Technical Summary
Existing hot-dip galvanizing processes suffer from incomplete coating, resulting in discontinuous coatings that cannot effectively prevent oxidation of steel parts and affect their corrosion resistance.
The fluxing solution, composed of zinc chloride, ammonium chloride, potassium fluoride, and a composite surfactant, decomposes at high temperature to generate NH3 and HCl gases, which purify the substrate surface and form a uniform crystalline salt film, improving the wettability of the workpiece with the zinc solution. The addition of composite surfactants and modified chitosan reduces surface tension and ensures coating uniformity.
It effectively reduces plating defects, improves the uniformity and corrosion resistance of the coating, ensures coating quality and anti-corrosion performance, and meets the high-efficiency process requirements of green production.
Smart Images

Figure BDA0004290333040000071 
Figure BDA0004290333040000081
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of hot-dip galvanizing, and more particularly to a plating aid liquid for hot-dip galvanizing process, a preparation method thereof and a hot-dip galvanizing process. BACKGROUND
[0002] Corrosion is one of the main forms of failure of steel materials, and therefore the research on metal corrosion and protection is of great significance. The hot-dip galvanizing alloy layer on the surface of steel can effectively improve the corrosion resistance of steel materials, and is therefore widely used in industrial production.
[0003] In the process of hot-dip galvanizing, the plating aid is an important treatment process, which generally involves immersing the steel workpiece after pickling in the plating aid for a period of time. After the plating aid, a salt film is formed on the surface, which can prevent the surface of the steel workpiece from being oxidized, and has a further cleaning effect on the surface of the workpiece. The plating aid is rapidly decomposed after entering the alloy plating liquid, and the active substrate and the plating liquid undergo subsequent alloy reaction to complete the galvanizing.
[0004] The zinc chloride + ammonium chloride plating aid process has been widely used by hot-dip galvanizing enterprises, but the applicant has found that the salt film formed by the plating aid has poor quality and is not continuous, and the steel surface in local areas cannot be immersed between the zinc liquid, cannot react, and cannot form a galvanizing layer, resulting in plating leakage. SUMMARY
[0005] In order to reduce the plating leakage phenomenon and improve the corrosion resistance of the workpiece, the present application provides a plating aid liquid for hot-dip galvanizing process, a preparation method thereof and a hot-dip galvanizing process.
[0006] In the first aspect, the present application provides a plating aid liquid for hot-dip galvanizing process, which adopts the following technical scheme:
[0007] A plating aid liquid for hot-dip galvanizing process, comprising the following raw materials by weight: zinc chloride 80-90 parts, ammonium chloride 40-50 parts, potassium fluoride 15-25 parts, composite surfactant 550-600 parts, and water 500-600 parts.
[0008] By adopting the above technical scheme, the plating aid liquid forms a plating aid film on the surface of the workpiece, and then in the process of hot-dip plating, the ammonium chloride rapidly decomposes into NH3 and HCl at high temperature; the generated HCl gas makes the surface of the substrate acidic, which can dissolve the ferrous oxide and the zinc oxide on the surface of the zinc liquid, purifying the interface between the substrate and the zinc liquid; and in the process of immersion plating, the gas NH3 and zinc generate H2 at high temperature, which causes a micro-explosion phenomenon on the surface of the substrate, further removing the oxide film on the surface of the substrate, purifying the surface of the substrate and reducing the plating leakage phenomenon; in the process of plating aid, the zinc chloride adheres to the surface of the workpiece to form a crystalline salt film, which isolates the workpiece from the air and reduces the secondary oxidation of the workpiece before immersion in the zinc liquid; the zinc chloride also has the effect of purifying the zinc liquid, which can react with the dross FeZn13 The reaction occurs at a higher temperature, reducing the plating leakage and improving the plating quality; the potassium fluoride can make the plating aid adhere uniformly on the substrate, protecting the substrate from oxidation; meanwhile, the surface activity of the substrate is maintained, the metal liquid's wettability to the workpiece surface is improved, the plating leakage is prevented, the plating layer is smooth, and the plating quality is improved.
[0009] The composite surfactant can improve the surface activity of the workpiece, reduce the surface tension of the zinc plating liquid, improve the wettability of the zinc plating liquid to the steel plate substrate, prevent the clean workpiece surface obtained by degreasing and rust removal from being oxidized again, reduce the plating leakage, and improve the plating quality.
[0010] Preferably, the composite surfactant includes anhydrous ethanol, alkyl phenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride, and chitosan in a weight ratio of 1:(1.5-2):(1.5-2):(1-1.5).
[0011] By adopting the above technical solution, the alkyl phenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride, and chitosan are dissolved in anhydrous ethanol, wherein the alkyl phenol polyoxyethylene ether and chitosan serve as non-ionic surfactants, and the tetradecyl dimethyl benzyl ammonium chloride serves as a cationic surfactant. After mixing, a composite surfactant with low foam and good water solubility can be obtained, the surface tension of the solution is further reduced, the wettability and permeability of the aid solution and the workpiece are improved, the film formation is more uniform and continuous, the plating leakage is reduced, and the plating quality is improved.
[0012] Preferably, the chitosan is a polyethylene glycol chitosan obtained by polyethylene glycol etherification grafting of chitosan.
[0013] Preferably, the preparation method of the polyethylene glycol chitosan is as follows:
[0014] 1) Polyethylene glycol oxidation
[0015] Acetic anhydride and polyethylene glycol are mixed, then sodium nitrite is added, stirring is performed for reaction, after the reaction is completed, white powder solid is obtained by suction filtration; the white powder solid is dissolved in anhydrous ethanol, then colorless transparent filtrate is obtained by suction filtration, the solvent is removed by rotary evaporation, and then drying is performed to obtain oxidized polyethylene glycol;
[0016] 2) Chitosan modification
[0017] Chitosan is dissolved in acetic acid to obtain a chitosan solution, the oxidized polyethylene glycol obtained in step 1) is added to the chitosan solution, and reaction is performed at 25-27°C for 24-25h to obtain a reaction liquid, the pH value of the reaction liquid is adjusted to 7, then suction filtration is performed, the filtrate is concentrated by rotary evaporation, dialysis is performed, and freeze-drying is performed to obtain polyethylene glycol chitosan.
[0018] By adopting the technical scheme, the chitosan is etherified and grafted with polyethylene glycol, the polyethylene glycol chitosan obtained has a lower surface tension, which is conducive to further reducing the surface tension of the solution, improving the wettability and permeability of the auxiliary solution and the workpiece, making the film forming more uniform and continuous, reducing the plating leakage and improving the plating layer quality. In addition, the polyethylene glycol chitosan has better loading, can load the zinc ions in the plating auxiliary solution, slowly release the zinc ions, keep the zinc ion concentration in the solution stable, make the plating auxiliary film on the surface of the workpiece more uniform, and is not easy to form local bubbles and inclusions, thereby reducing the plating leakage.
[0019] Preferably, the weight ratio of the polyethylene glycol to the chitosan is (12-15):1.
[0020] By adopting the technical scheme, the ratio of the polyethylene glycol to the chitosan is controlled, so as to control the grafting amount of the polyethylene glycol in the synthesized polyethylene glycol chitosan, thereby regulating the surface tension and the loading force of the polyethylene glycol chitosan, making the surface tension and the loading force of the polyethylene glycol chitosan reach a relatively more balanced state, making the plating auxiliary film on the surface of the workpiece more uniform, and not easy to form local bubbles and inclusions, thereby reducing the plating leakage.
[0021] Preferably, it further includes 10-15 parts of cerium chloride.
[0022] By adopting the technical scheme, the cerium chloride can effectively improve the surface layer quality of the plating layer by catalyzing and cooperating with the zinc chloride.
[0023] Preferably, it further includes 8-10 parts of zinc phytate.
[0024] By adopting the technical scheme, the zinc phytate can avoid the secondary oxidation of the activated workpiece, ensure that the workpiece still has a clean surface when immersed in the zinc plating solution again, reduce impurities, and thereby reduce the plating leakage.
[0025] In the second aspect, the application provides a preparation method of a plating auxiliary solution for hot galvanizing process, which adopts the following technical scheme:
[0026] The preparation method of the plating auxiliary solution for hot galvanizing process includes the following steps:
[0027] A1. Dissolving the raw materials except the composite surfactant in water to obtain a mixed solution;
[0028] A2. Adding the composite surfactant to the mixed solution to obtain the plating auxiliary solution for hot galvanizing process.
[0029] By adopting the technical scheme, the preparation method of the application is simple and easy to operate, has no special requirements for production equipment, and is suitable for industrial production.
[0030] In the third aspect, the application provides a hot galvanizing process, which adopts the following technical scheme:
[0031] A hot galvanizing process, comprising the following steps: S1. alkali washing; S2. pickling; S3. plating aid; S4. hot galvanizing; the plating aid solution is the plating aid solution used in any of the above hot galvanizing processes;
[0032] The S3 plating aid is: immersing the workpiece after alkali washing and pickling in the plating aid solution for 30-35s, the temperature of the plating aid solution is 60-70℃, and after taking out, drying at 200-210℃ for 3-10min until completely dry.
[0033] By adopting the above technical scheme, the plating aid temperature can be any temperature between 60-70℃, such as 60℃, 65℃, 70℃; the plating aid time can be any time between 30-35s, such as 30s, 32s, 35s; the plating aid process can be completed within 30-35s, and the plating aid temperature is low, which can effectively improve the efficiency, save resources, and meet the green production concept.
[0034] In summary, the present application has the following beneficial effects:
[0035] 1. Since the present application uses zinc chloride, ammonium chloride, potassium fluoride, and a composite surfactant as a plating aid solution, ammonium chloride cleans the surface of the workpiece, zinc chloride reduces the secondary oxidation of the workpiece before immersion in the zinc solution and reduces the FeZn 13 reacts at a higher temperature, reducing plating leakage, potassium fluoride maintains the surface activity of the substrate, improving the wetting ability of the metal liquid to the surface of the workpiece, preventing plating leakage, the composite surfactant can improve the surface activity of the workpiece, reduce the surface tension of the zinc plating solution, improve the wettability of the zinc plating solution to the steel plate substrate, prevent the clean workpiece surface obtained after degreasing and rust removal from being oxidized again, and reduce plating leakage; using the plating aid solution of the present application for hot galvanizing, the obtained plating layer has high uniformity and strong corrosion resistance.
[0036] 2. The present application preferably uses alkyl phenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride, and chitosan as a composite surfactant, and modifies chitosan with polyethylene glycol to further reduce the surface tension of the solution, improve the wettability and permeability of the aid solution and the workpiece, make the film more uniform and continuous, reduce plating leakage, and improve the quality of the plating layer.
[0037] 3. In the present application, zinc phytate is preferably added, the workpiece after activation is oxidized again, ensuring that the workpiece remains clean when immersed in the zinc plating solution again, reducing impurity points, reducing plating leakage, and improving the quality of the plating layer. DETAILED DESCRIPTION
[0038] The present application is further described in detail below in conjunction with the examples.
[0039] Preparation examples of raw materials and intermediates
[0040] Raw materials
[0041] The raw materials of the embodiments of the present application can be obtained commercially:
[0042] Zinc chloride, industrial grade;
[0043] Ammonium chloride, industrial grade;
[0044] Potassium fluoride, industrial grade;
[0045] Anhydrous ethanol, analytical pure;
[0046] Alkyl phenol polyoxyethylene ether, model OP-10;
[0047] Tetradecyl dimethyl benzyl ammonium chloride, analytical pure;
[0048] Chitosan, Mw50 000, degree of deacetylation 92%;
[0049] Polyethylene glycol, molecular weight 400;
[0050] Acetic anhydride, analytical pure;
[0051] Sodium nitrite, analytical pure;
[0052] Cerium chloride, analytical pure;
[0053] Zinc phytate, analytical pure;
[0054] Acetic acid, analytical pure.
[0055] Preparation Example
[0056] Preparation Example 1
[0057] A polyethylene glycol chitosan, the preparation method thereof is:
[0058] 1) Polyethylene glycol oxidation
[0059] 5 kg of acetic anhydride, 12 kg of polyethylene glycol were mixed, then 7 kg of sodium nitrite was added, stirred for 3 min, after the reaction was completed, white powder solid was obtained by suction filtration; the white powder solid was dissolved with anhydrous ethanol, and colorless transparent filtrate was obtained by suction filtration, and the solvent was removed by rotary evaporation and then dried to obtain oxidized polyethylene glycol;
[0060] 2) Chitosan modification
[0061] 1 kg of chitosan was dissolved in 50 L of 2% acetic acid solution to obtain a chitosan solution, and the oxidized polyethylene glycol obtained in step 1) was added to the chitosan solution, and reacted at 25°C for 24 h to obtain a reaction solution, then the pH value of the reaction solution was adjusted to 7, and then suction filtration was performed, the filtrate was concentrated by rotary evaporation, and then the solution was dialyzed in a dialysis bag with a molecular weight cutoff of 10k for 48 h, and then freeze-dried to obtain polyethylene glycol chitosan.
[0062] Preparation Example 2
[0063] Different from Preparation Example 1, the amount of polyethylene glycol used in Preparation Example 2 is 15 kg.
[0064] Preparation Example 3
[0065] Different from Preparation Example 1, the amount of polyethylene glycol used in Preparation Example 3 is 10 kg.
[0066] Preparation Example 4
[0067] Different from Preparation Example 1, the amount of polyethylene glycol used in Preparation Example 4 is 20 kg.
[0068] Example
[0069] Examples 1-3
[0070] A plating aid solution for hot galvanizing process is prepared by the following method:
[0071] A1. Dissolve the raw materials except the composite surfactant in water according to the proportion in Table 1 to obtain a mixed solution;
[0072] A2. Add the composite surfactant to the mixed solution according to the proportion in Table 1, and mix to obtain the plating aid solution for hot galvanizing process.
[0073] Table 1 Raw material proportion table (kg) for Examples 1-3
[0074] Example 1 Example 2 Example 3 Zinc chloride 80 85 90 Ammonium chloride 50 45 40 Potassium fluoride 15 20 25 Complexing surfactant 600 570 550 Water 500 550 600
[0075] The composite surfactant includes anhydrous ethanol, alkyl phenol polyoxyethylene ether, and tetradecyl dimethyl benzyl ammonium chloride in a weight ratio of 1:1.5:1.5.
[0076] Example 4
[0077] Different from Example 2, the composite surfactant in Example 4 includes anhydrous ethanol, alkyl phenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride, and chitosan in a weight ratio of 1:1.5:2:1.
[0078] Example 5
[0079] Different from Example 2, the composite surfactant in Example 5 includes anhydrous ethanol, alkyl phenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride, and chitosan in a weight ratio of 1:2:1.5:1.5.
[0080] Example 6
[0081] Different from example 2, the composite surfactant in example 6 comprises anhydrous ethanol, alkylphenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride and chitosan in a weight ratio of 1:2:1.5:2.
[0082] Examples 7-10
[0083] Different from example 5, the chitosan in examples 7-10 is respectively replaced by an equal amount of pegylated chitosan from preparation examples 1-4.
[0084] Examples 11-13
[0085] Different from example 8, examples 11-13 further respectively comprise 10 kg, 15 kg, 20 kg of cerium chloride.
[0086] Examples 14-16
[0087] Different from example 12, examples 14-16 further respectively comprise 8 kg, 10 kg, 12 kg of zinc phytate.
[0088] Comparative examples
[0089] Comparative example 1
[0090] Different from example 1, comparative example 1 uses an equal amount of zinc chloride to replace potassium fluoride.
[0091] Comparative example 2
[0092] Different from comparative example 1, the surfactant in comparative example 2 is anhydrous ethanol and alkylphenol polyoxyethylene ether in a weight ratio of 1:1.5.
[0093] Comparative example 3
[0094] Different from comparative example 1, the surfactant in comparative example 3 is anhydrous ethanol and tetradecyl dimethyl benzyl ammonium chloride in a weight ratio of 1:1.5.
[0095] Application examples
[0096] Application example 1
[0097] A hot galvanizing process, comprising the following steps:
[0098] S1. Alkaline cleaning
[0099] The workpiece is treated with a 10% by mass sodium hydroxide solution for 20 min;
[0100] S2. Acid cleaning
[0101] The alkaline cleaned workpiece obtained in step S1 is treated with a 10% by mass hydrochloric acid solution for 40 min;
[0102] S3. Assisted plating
[0103] The pickled workpiece obtained in step S2 was immersed in the assisted plating solution obtained in Example 1 for 30 s, and the temperature of the assisted plating solution was 70°C. After being taken out, the workpiece was dried at 200°C for 5 min until completely dry.
[0104] S4. Hot galvanizing
[0105] The dried workpiece in step S3 was put into molten zinc solution, and the temperature of the zinc solution was controlled at 440°C. The residence time was controlled at 40 s to obtain a hot plated workpiece.
[0106] S5. The hot plated workpiece was slowly led out, and the excess zinc solution on the surface of the workpiece was allowed to naturally flow back.
[0107] Application Example 2-16
[0108] Different from Application Example 2, the assisted plating solution in Application Example 2-16 was obtained from Example 2-16, respectively.
[0109] Comparative Application Example
[0110] Comparative Application Example 1-3
[0111] Different from Application Example 1, the assisted plating solution in Comparative Application Example 1-3 was obtained from Comparative Example 1-3, respectively.
[0112] Performance detection test
[0113] Detection method / test method
[0114] The coatings in the application examples and the application comparative examples were subjected to the following performance detection, and the detection results are shown in Table 2:
[0115] Corrosion resistance: The neutral salt spray test was carried out according to the method of Standard for Neutral Salt Spray Test of Metal Coating GB / 6458-86. The rusting of the coating on the surface of the workpiece was observed after 300 h, and the area ratio of the rusted area was recorded.
[0116] Coating uniformity test: The test was carried out according to the method described in the document "Report on Test of Coating Uniformity and Deep Plating Capacity Reporter: Zhou Yingchun Date: 2013 / 1 / 15". Test plates with an opening size of 24.5*20.5 mm, a plate thickness of 1.5 mm, and a quantity of 16 PNL were prepared. The test plate drill serial number was ME-TEST001, and holes with different diameters of 0.25-0.35 mm were drilled. Eight PNL plates were hung per fly, the thickness of the measurement surface was numbered, and single-sided measurement was distinguished. Each PNL plate was measured at 28 points on one side.
[0117] Table 2 Performance detection results
[0118]
[0119]
[0120] It can be seen from the combination of Examples 1-16 and Comparative Examples 1-3 and Table 2 that the area of the workpiece surface producing rust spots after the coating layer in Examples 1-16 is subjected to neutral salt spray corrosion for 300 h is lower than that of Comparative Examples 1-3; the uniformity of the coating layer in Examples 1-16 is higher than that of Comparative Examples 1-3, which indicates that the plating aid solution prepared in the application has better plating aid effect, less plating omission and higher coating quality.
[0121] It can be seen from the combination of Example 1 and Comparative Example 1 and Table 2 that the uniformity of the coating layer in Example 1 is higher than that of Comparative Example 1, and the area of the workpiece surface producing rust spots after the coating layer in Example 1 is subjected to neutral salt spray corrosion for 300 h is far lower than that of Comparative Example 1, which indicates that the addition of potassium fluoride can improve the uniformity of the coating layer and improve the coating quality; this may be because the potassium fluoride can make the plating aid adhere uniformly on the substrate to form a dense oxide film to protect the substrate from being oxidized; at the same time, the potassium fluoride can keep the surface activity of the substrate and improve the wetting ability of the metal liquid to the surface of the workpiece to prevent plating omission, make the coating layer smooth and improve the coating quality.
[0122] It can be seen from the combination of Examples 1-3 and Table 2 that the raw material ratio in the plating aid solution will affect the corrosion resistance of the coating layer, and the raw material ratio in Example 2 is more optimal.
[0123] It can be seen from the combination of Example 2 and Examples 4-6 and Table 2 that the ratio of the composite surfactant will affect the quality of the coating layer, which may be because within the ratio range of the composite surfactant defined in the application, the obtained surfactant can further reduce the surface tension of the solution, improve the wettability and permeability of the aid solution and the workpiece, make the film more uniform and continuous, reduce plating omission and improve the coating quality.
[0124] It can be seen from the combination of Example 5 and Examples 7-10 and Table 2 that the uniformity of the coating layer in Examples 7-10 is higher than that of Example 5, and the area of the workpiece surface producing rust spots after the coating layer in Examples 7-10 is subjected to neutral salt spray corrosion for 300 h is far lower than that of Example 5, which indicates that the modification treatment of chitosan with polyethylene glycol can improve the uniformity and corrosion resistance of the coating layer; this may be because the chitosan is etherified and grafted with polyethylene glycol to obtain polyethylene glycol chitosan with lower surface tension, which is conducive to further reducing the surface tension of the solution, improving the wettability and permeability of the aid solution and the workpiece, making the film more uniform and continuous; in addition, the polyethylene glycol chitosan has better loading, can load zinc ions in the plating aid solution, makes the zinc ions slowly release, keeps the zinc ion concentration in the solution stable, makes the plating aid film on the surface of the workpiece more uniform, is not easy to form local bubbles and inclusions, reduces plating omission and improves the coating quality.
[0125] In combination with Example 8 and Examples 11-13, and in combination with Table 2, it can be seen that the addition of cerium chloride can further improve the uniformity and corrosion resistance of the coating.
[0126] In combination with Examples 14-16 and Example 12, and in combination with Table 2, it can be seen that the addition of zinc phytate can further improve the uniformity and corrosion resistance of the coating, which can be because zinc phytate can avoid the secondary oxidation of the activated workpiece, ensure that the workpiece remains clean when re-immersed in the zinc plating solution, reduce impurity points, thereby reducing plating leakage and improving the quality of the coating.
[0127] The specific embodiments are only an explanation of the present application, which is not a limitation of the present application, and those skilled in the art can make modifications to the embodiments without creative contribution after reading the specification, but as long as the scope of the claims of the present application is within the protection of the Patent Law.
Claims
1. A plating aid solution for a hot-dip galvanizing process, characterized by comprising: a zinc salt; a sulfur compound; and a phosphorus compound. The raw materials include the following components by weight: zinc chloride 80-90 parts, ammonium chloride 40-50 parts, potassium fluoride 15-25 parts, composite surfactant 550-600 parts, water 500-600 parts, cerium chloride 10-15 parts, and zinc phytate 8-10 parts; The composite surfactant comprises anhydrous ethanol, alkyl phenol polyoxyethylene ether, tetradecyl dimethyl benzyl ammonium chloride, and chitosan in a weight ratio of 1: (1.5-2): (1.5-2): (1-1.5); The chitosan is polyethylene glycolated chitosan obtained by polyethylene glycol etherification grafting of chitosan; The preparation method of the polyethylene glycolated chitosan is as follows: 1) polyethylene glycol oxidation Acetic anhydride and polyethylene glycol are mixed, then sodium nitrite is added, and the mixture is stirred and reacted. After the reaction is completed, the white powder solid is obtained by suction filtration. The white powder solid is dissolved in anhydrous ethanol, and the colorless transparent filtrate is obtained by suction filtration. The solvent is removed by rotary evaporation and concentration, and then dried to obtain oxidized polyethylene glycol; 2) chitosan modification Chitosan is dissolved in acetic acid to obtain a chitosan solution. The oxidized polyethylene glycol obtained in step 1) is added to the chitosan solution, and the mixture is reacted at 25-27℃ for 24-25h to obtain a reaction solution. The pH value of the reaction solution is adjusted to 7, and then suction filtration is performed. The filtrate is concentrated by rotary evaporation, dialyzed, and freeze-dried to obtain polyethylene glycolated chitosan. The weight ratio of polyethylene glycol to chitosan is (12-15):
1.
2. A method for preparing the plating aid solution for hot galvanizing according to any one of claims 1, characterized by, The method comprises the following steps: A1. Dissolving the raw materials except the composite surfactant in water to obtain a mixed solution; A2. Adding the composite surfactant to the mixed solution to obtain a plating aid solution for hot galvanizing process.
3. A hot dip galvanizing process comprising the steps of: S1. Alkaline cleaning; S2. Acid cleaning; S3. Plating aid; S4. Hot galvanizing; characterized in that: the plating aid solution is the plating aid solution for hot galvanizing process according to any one of claims 1-2; The S3 plating aid is: immersing the workpiece subjected to alkaline cleaning and acid cleaning in the plating aid solution for 30-35s, and the temperature of the plating aid solution is 60-70℃. After taking out, drying at 200-210℃ for 3-10min until completely dry.
Citation Information
Patent Citations
On-batch steel hot galvanizing environment-friendly type multi-effect galvanization helping liquid and use method thereof
CN104195487A
Plating assistant agent for zinc-aluminum-nickel-rare earth-alloy hot-dip plating and technological method
CN105908113A
Preparation method of chitosan derivative for salt-free dyeing of reactive dye
CN106699923A
Smokeless flux for hot dipping and preparation method thereof
CN108842120A
Plating assistant solution and hot galvanizing process using same
CN112126876A